Do different sexes, skeletal and breathing patterns influence the maxillary sinuses volume? A retrospective study. (December 2021) - Miranda-Viana, Murilo; Freitas, Deborah Queiroz; Machado, Alessiana Helena; Gomes, Amanda Farias; Nejaim, Yuri
Highlights: There is a correlation between the morphometry of the maxillary sinuses and sexes. There is no correlation between the morphometry of the maxillary sinuses and the skeletal malocclusions and facial types. There is no correlation between the morphometry of the maxillary sinuses and the breathing pattern. CBCT is the choice of imaging exam to evaluate maxillary sinuses with three-dimensional view. Abstract: Objectives: To assess the influence of sex, skeletal malocclusion, facial type, and breathing pattern on the volume of the maxillary sinuses. Materials and Methods: Images of cone beam computed tomography of 212 individuals (104 males and 108 females) were classified in relation to skeletal malocclusion (class I, II, or III), facial type (brachycephalic, mesocephalic, or dolichocephalic), and breathing pattern (nasal or oral breathing). The volume of the maxillary sinuses of each individual was achieved through segmentation by using the ITK-SNAP software. The images were evaluated by two radiologists, independently, in a quiet and low-light room, using a monitor with high resolution. Data were subjected to multi-way analysis of variance, considering a significance level of 5% ( α  = 0.05). Results: The intra- and interevaluator agreement values varied from 0.97 to 0.99, and from 0.96 to 0.99, respectively. The volume of the maxillary sinuses was significantly greater in males than in females (p < 0.0001). Skeletal malocclusion, facial type and breathing pattern did not influence the maxillary sinuses volume (p > 0.05). Conclusions: The volume of the maxillary sinuses may be a useful tool to differentiate sexes. Skeletal malocclusion, facial type, and breathing pattern do not influence the maxillary sinuses volume.